Omega-3 and DHA Supplementation in Pregnancy: A Systematic Review of Its Role in Preventing Preeclampsia and Gestational Diabetes - Deni Wirhana; Bayu Setyo Nugroho; Tuswandi Ahmad Waly (The International Journal of Medical Science and Health Research, 2025)
Background: Omega-3 fatty acids, such as docosahexaenoic acid (DHA), plays a crucial role in fetal development and pregnancy maintenance, potentially reducing the risk of complications like gestational diabetes mellitus (GDM) and preeclampsia. Supplementation of these fatty acids may improve pregnancy outcomes by promoting fetal growth, prolonging gestational age, and positively influencing neonatal birth weight. However, the clinical evidence supporting the role of omega-3 supplementation in preventing preeclampsia and GDM remains inconclusive. Methods: A preliminary database search identified over 100 relevant studies. Following a rigorous three-stage screening process, eight studies meeting the predefined inclusion criteria were selected for in-depth analysis. Each underwent a comprehensive critical assessment to examine the impact of Omega-3 and DHA supplementation on preventing preeclampsia and gestational diabetes. This systematic approach ensured that the analysis was based on high-quality data, aligned with the study’s objectives, and provided meaningful insights. Result: The final selection comprised eight studies that met the inclusion criteria. A thorough evaluation of these studies allowed for an in-depth investigation of Omega-3 and DHA supplementation's role in preventing preeclampsia and gestational diabetes. This structured analysis reinforced the study’s reliability, ensuring that conclusions were drawn from robust and credible evidence. Conclusion: DHA supplementation plays a crucial role in pregnancy, supporting placental function and maternal metabolic health. However, its preventive role in preventing preeclampsia and GDM remains uncertain. Future research should explore potential benefits and evidence-based guidelines.